The Role of Sampling Data as Evidence in Judicial and Administrative Proceedings (Book). - Trueblood, Robert M. (The Accounting Review, 1955)
Reviews the book "The Role of Sampling Data as Evidence in Judicial and Administrative Proceedings," by Joel Dean, W. Edwards Deming.